Managing power consumption in networks on chips. - Simunic, T. (IEEE Transactions on VLSI systems)
In this paper, we present a new methodology for managing power consumption of networks-on-chips (NOCs). A power management problem is formulated for the first time using closed-loop control concepts. We introduce an estimator and a controller that implement our power management methodology. The estimator is capable of very fast and accurate tracking of changes in the system parameters. Parameters estimated are used to form the system model. Our system model combines node and network centric power management decisions. Node centric power management assumes no a priori knowledge of requests coming in from outside the core. Thus, it implements a more traditional dynamic voltage scaling and power management control algorithms. Network-centric power management utilizes interaction with the other system cores regarding the power and the quality of service (QoS) needs. The overall system model is based on Renewal theory and, thus, guarantees globally optimal results. We introduce a fast optimization method that runs multiple orders of magnitude faster than the previous optimization approaches while still having the same accuracy in obtaining the power management control. Finally, our controller implements the results of optimization in either hardware or software. The new methodology for power management of NOCs is tested on a system consisting of four satellite units, each implementing an estimator and a controller capable of both node and network centric power management. Our results show large savings in power with good QoS.